The Influence of Profitability on Company Value With Company Size as An Intervening Variable in Telecommunications Companies Listed on The BEI - Utomo, Agus Setyo; Partini, Sri (International Journal of Seocology, 2023)
The phenomenon that occurred during the Covid 19 pandemic was that many telecommunications companies that went public developed well, whereas during the pandemic, on the other hand, many companies experienced large losses and even went bankrupt. The problem in this research aims to determine the effect of profitability on company value with company size as an intervening variable in telecommunications companies listed on the IDX for the 2019-2021 period. The type of research used is quantitative research with secondary data sources. The population in this research is 19 telecommunications service companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample was taken using a purposive sampling technique as many as 16 companies that met the criteria. The data analysis technique uses regression analysis techniques with path analysis. The research results show that profitability has an effect on company size, company size has no effect on company value, and profitability has no effect on company value through company size.